Dual-Specificity Phosphatase 3 Deficiency or Inhibition Limits Platelet Activation and Arterial Thrombosis. Issue 7 (17th February 2015) - Musumeci, Lucia; Kuijpers, Marijke J.; Gilio, Karen; Hego, Alexandre; Théâtre, Emilie; Maurissen, Lisbeth; Vandereyken, Maud; Diogo, Catia V; Lecut, Christelle; Guilmain, William; Bobkova, Ekaterina V.; Eble, Johannes A.; et al.
<x xml:space="preserve">Abstract</x> Background— A limitation of current antiplatelet therapies is their inability to separate thrombotic events from bleeding occurrences. A better understanding of the molecular mechanisms leading to platelet activation is important for the development of improved therapies. Recently, protein tyrosine phosphatases have emerged as critical regulators of platelet function. Methods and Results— This is the first report implicating the dual-specificity phosphatase 3 (DUSP3) in platelet signaling and thrombosis. This phosphatase is highly expressed in human and mouse platelets. Platelets from DUSP3-deficient mice displayed a selective impairment of aggregation and granule secretion mediated by the collagen receptor glycoprotein VI and the C-type lectin-like receptor 2. DUSP3-deficient mice were more resistant to collagen- and epinephrine-induced thromboembolism compared with wild-type mice and showed severely impaired thrombus formation on ferric chloride–induced carotid artery injury. Intriguingly, bleeding times were not altered in DUSP3-deficient mice. At the molecular level, DUSP3 deficiency impaired Syk tyrosine phosphorylation, subsequently reducing phosphorylation of phospholipase Cγ2 and calcium fluxes. To investigate DUSP3 function in human platelets, a novel small-molecule inhibitor of DUSP3 was developed. This compound specifically inhibited collagen- and C-type lectin-like receptor 2–induced human platelet aggregation, thereby phenocopying the effect of DUSP3 deficiency in murine cells. Conclusions— DUSP3 plays a selective and essential role in collagen- and C-type lectin-like receptor 2–mediated platelet activation and thrombus formation in vivo. Inhibition of DUSP3 may prove therapeutic for arterial thrombosis. This is the first time a protein tyrosine phosphatase, implicated in platelet signaling, has been targeted with a small-molecule drug.